Microbial Array And Antibiotic Sensitivity Pattern Of Catheter Related Blood-Stream Infection At A Tertiary Care Hospital In South India - PRACHI SHAW; CHANDAN KUMAR SHAW; K. SAILEELA (International Journal of Pharma and Bio Sciences, 2012)
Epidemiological data regarding catheter related blood stream infections (CRBI) in developing countries are scarce and essential to fabricate infection control and antibiotic prescription policies. Intravenous (IV) catheter tips and two synchronous blood samples from 297 patients with intravenous catheters and ≥ 48 hours stay were subjected to culture and sensitivity. Concurrent isolation of the same organism from both blood samples and catheter tips as well as same sensitivity pattern was considered significant for CRBI. The microbial array of CRBI was clinically correlated with age, clinical signs and symptoms and mortality. Out of the 297 cases studied 21.2% were associated with CRBI. Out of the positive 183 isolates S. epidermidis accounted for most [62 i.e. (34.4%)] of the isolates from I.V. Catheter tips while P. aeruginosa [67 (36.6%)] was the commonest isolate from the blood. The incidence of CRBI’s due to S. epidermidis P. aeruginosa, Klebsiella spp., S. aureus, E. coli was 12.8%, 3.4%, 1.7%, 1.7% and 1% respectively. The isolation rate of all organisms in cases of septicemia (261) due to CRBI was 18.8%. Fourteen asymptomatic cases had CRBI - all due to S. epidermidis. S. epidermidis was most prevalent in all age groups. Among the isolates associated with CRBI, S. epidermidis were sensitive to vancomycin (100%) and resistant to most other dugs. Eighty percent of the S. aureus associated with CRBI were MRSA while 62% of the gram negative organisms were ESBL producing. Microbial spectrum and the sensitivity pattern of CRBI observed may be used to formulate stricter infection control and antibiotic policy in view of resistance to second line antibiotics.